To Waste or Not to Waste: Questioning Potential Health Risks of Micro- and Nanoplastics with a Focus on Their Ingestion and Potential Carcinogenicity - Elisabeth S. Gruber; Vanessa Stadlbauer; Verena Pichler; Katharina Resch-Fauster; Andrea Todorovic; Thomas C. Meisel; Sibylle Trawoeger; Oldamur Hollóczki; Suzanne D. Turner; Wolfgang Wadsak; A. Dick Vethaak; Lukas Kenner (Exposure and Health, 2023)
Micro- and nanoplastics (MNPs) are recognized as emerging contaminants, especially in food, with unknown health significance. MNPs passing through the gastrointestinal tract have been brought in context with disruption of the gut microbiome. Several molecular mechanisms have been described to facilitate tissue uptake of MNPs, which then are involved in local inflammatory and immune responses. Furthermore, MNPs can act as potential transporters (“vectors”) of contaminants and as chemosensitizers for toxic substances (“Trojan Horse effect”). In this review, we summarize current multidisciplinary knowledge of ingested MNPs and their potential adverse health effects. We discuss new insights into analytical and molecular modeling tools to help us better understand the local deposition and uptake of MNPs that might drive carcinogenic signaling. We present bioethical insights to basically re-consider the “culture of consumerism.” Finally, we map out prominent research questions in accordance with the Sustainable Development Goals of the United Nations.

Cardioembolic Ischemic Stroke Gene Expression Fingerprint in Blood: a Systematic Review and Verification Analysis - Teresa García-Berrocoso; Elena Palà; Marta Consegal; Benedetta Piccardi; Alex Negro; Natalia Gill; Anna Penalba; Hector Huerga Encabo; Israel Fernández-Cadenas; Andreas Meisel; Christian Meisel; Glen C. Jickling; et al. (Translational Stroke Research, 2020)

Neuronal Nitric Oxide Synthase is a Key Factor in Doxorubicin-Induced Toxicity to Rat-Isolated Cortical Neurons - Miguel Ângelo Lopes; Andreas Meisel; Félix Dias Carvalho; Maria de Lourdes Bastos (Neurotoxicity Research, 2011)

Molecular and Cellular Mechanisms of Ecstasy-Induced Neurotoxicity: An Overview - João Paulo Capela; Helena Carmo; Fernando Remião; Maria Lourdes Bastos; Andreas Meisel; Félix Carvalho (Molecular Neurobiology, 2009)

Brain antigens in functionally distinct antigen-presenting cell populations in cervical lymph nodes in MS and EAE - Marloes van Zwam; Ruth Huizinga; Marie-José Melief; Annet F. Wierenga-Wolf; Marjan van Meurs; Jane S. Voerman; Knut P. H. Biber; Hendrikus W. G. M. Boddeke; Uta E. Höpken; Christian Meisel; Andreas Meisel; Ingo Bechmann; et al. (Journal of Molecular Medicine, 2009)

Association of MDR1 genotypes with susceptibility to colorectal cancer in older non-smokers - Elena Osswald; Andreas Johne; Gabriele Laschinski; Farhad Arjomand-Nahad; Uwe Malzahn; Julia Kirchheiner; Thomas Gerloff; Christian Meisel; Przemyslaw M. Mrozikiewicz; Jury Chernov; Ivar Roots; Karla Köpke (European Journal of Clinical Pharmacology, 2006)

Pathophysiology of Stroke: Lessons from Animal Models - Philipp Mergenthaler; Ulrich Dirnagl; Andreas Meisel (Metabolic Brain Disease, 2004)